ON ISOMORPHIC SOFT LATTICES AND SOFT SUBLATTICES (FUDMA JOURNAL OF SCIENCES, 2023)
This paper crisply presents the fundamentals of soft set theory to emphasize that soft set has enough developed basic supporting tools through which various algebraic structures in theoretical point of view could be developed. We defined the term soft lattice and present the concept of upper bound and least upper bound, lower bound and greatest lower bound in terms of soft set context. Soft lattice is redefined in terms of supremum and infimum and some related results are established. A perception named isomorphic soft lattice and soft sublattice are introduced where some related results are established.
Keywords: Soft set, Parameters, soft Lattice, isomorphic soft lattice and soft sublattice